Synthesis and characterization of a novel quaternary copolymerized thermoplastic copolyimide with excellent heat resistance, thermoplasticity, and solubility - X. W. Cao; C. Wei; G. J. He; X. Liu (eXPRESS Polymer Letters)
A series of novel quaternary copolymerized thermoplastic polyimides were successfully prepared with asymmetric diahydride: 3,4′-oxydiphthalic anhydride (a-ODPA) and symmetric anhydride: 4,4′-oxydiphthalicanhydride (s-ODPA), 9,9′-bis(4-aminophenyl)fluorene (BAFL) and 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) as diamine. The synergistic effect of non-coplanar structure, fluorenyl cardo groups, methyl groups and flexible groups on the solubility, heat resistance and thermoplasticity of polyimide was discussed. The experimental results showed that the addition of BAFL greatly improved the heat resistance of polyimide. The glass transition temperature (Tg) of PI-A~PI-E with different ratios were 235.3–305.5 °C. Compared with control group PI-F, PI-A~PI-E were completely soluble within 3 h in DMF, DMAc, NMP, showing that they had excellent solubility, and what’s more, under the synergistic effect, the thermoplasticity of PI-A~PI-E was also greatly improved.